2009
DOI: 10.1177/0272989x09336075
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Constraints and Cost-Effectiveness: A Discrete Event Simulation for Drug-Eluting Stents

Abstract: Our model shows that neglected limited capacities can cause wrong cost-effectiveness results. Therefore, capacities should be explicitly included in decision-analytic models if there is evidence of scarcity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…RM performed at an aggregate level). Out of the 10 articles, 5 studies applied RM at an organisational level [19][20][21][22][23]] and 5 at a national level [24,[26][27][28][29].…”
Section: Searches and Siftingmentioning
confidence: 99%
See 3 more Smart Citations
“…RM performed at an aggregate level). Out of the 10 articles, 5 studies applied RM at an organisational level [19][20][21][22][23]] and 5 at a national level [24,[26][27][28][29].…”
Section: Searches and Siftingmentioning
confidence: 99%
“…Regarding the type of analyses, out of the 10 articles identified in the systematic review, only 1 article [21] includes RM aspects (i.e. resource constraints) in both CEA and BIA models, while the rest of the articles focus solely on CEA.…”
Section: Searches and Siftingmentioning
confidence: 99%
See 2 more Smart Citations
“…Jahn et al [34] showed in a case example for cost effectiveness of drug-eluting stents that neglected limited capacities can cause wrong results. They developed a DES model where resources capacities and dynamic waiting lines were explicitly modelled.…”
Section: Examples Of Resource Modelling At Individual Organisational mentioning
confidence: 99%